Population and Diversity of Soil and Leaf Litter Mesofauna in Arable Soils at The Agriculture Experimental Field of University of Lampung - Arif, Mas Achmad Syamsul; Niswati, Ainin; Yusnaini, Sri; Ardiyani, Novia Pratiwi (JOURNAL OF TROPICAL SOILS, 2017)
This research was conducted to study the population and diversity of soil and leaf litter mesofauna in arable soils under different types of vegetation and slope at the Agriculture Experimental Field (AEF) of University of Lampung. This study was designed to use the survey method. The soil and leaf litter samples were taken from different vegetation and slope classes. Observational variables included population and diversity index of soil mesofauna (H’), soil temperature, soil moisture content, soil pH, soil organic-C, soil total-N, and soil C/N ratio. The data of population distribution were presented in a boxplot diagram and the correlation between soil properties and mesofauna population or mesofauna diversity index were presented. The results showed that the most abundant soil mesofauna was observed in the plots with sugarcane vegetation, either sampled at the end of dry season (November 2015) or at the beginning of rainy season (April 2016). However, the highest number of leaf litter mesofauna was found in the plot with cassava vegetation. This result suggests that the cassava leaf litter most likely became the preferred substrate for mesofauna. In all treatments, the value of mesofauna diversity index (H‘) was categorized as low according to the Shannon-Weaver index. Two dominant orders frequently found in almost all vegetation types were Acarina and Collembola. The results of correlation analysis indicated that only soil pH sampled on November 2015 was positively correlated with the mesofauna population (range of pH 5.0 to 6.6). Soil moisture content sampled on November 2015 and soil C/N ratio sampled on April 2016 were positively correlated with the diversity index of soil mesofauna, respectively. Soil total-N sampled on November 2015 was negatively correlated with the soil mesofauna diversity index. The increase of leaf litter biomass appeared to promote the increase of the leaf litter mesofauna population, but not the diversity index.Keywords: diversity index, leaf litter, soil mesofauna, vegetation